2022
DOI: 10.1108/jamr-05-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking and WOM as moderators in the relationship between status consumption, brand image and purchase intention of counterfeit brand shoes

Abstract: PurposeThe study's objective is to examine the consumers' intention to buy counterfeit brand shoes. A conceptual model is developed to test the risk-taking and word-of-mouth (WOM) as a moderator in the relationship between status consumption, brand image, and consumer intention to buy counterfeit shoes.Design/methodology/approachBased on the theory of reasoned action (TRA) and signaling theory (ST), this research was conducted in the Indian National Capital Region. Using a structured instrument, the data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 103 publications
0
9
0
1
Order By: Relevance
“…In addition, this study confirmed the robustness of the basic TRA theory with respect to counterfeit purchase behavior having the strong explanatory power of attitude and subjective norm on purchase intention (66.9% in Omani sample and 74.4% in Qatari sample). Several previous studies in the counterfeit domain used TRA as a theoretical base and tried to extend the theory by examining the influencing factors of customer attitude towards counterfeiting, such as moral equity and relativism (Arli et al , 2015), idealism, relativism, religiosity and consumer ethics (Jiang et al , 2018), social influencing factors (information susceptibility and normative susceptibility) and personality factors (value consciousness, perceived risk, integrity, status consumption and materialism) (Ting et al , 2016), status consumption, risk taking and brand image (Patel et al , 2022). However, to the best our knowledge, the study is very limited addressing the effect of perceived social risk and perceived performance risk on the attitude formation in the domain of non-deceptive counterfeiting, particularly using the TRA as a theoretical anchor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study confirmed the robustness of the basic TRA theory with respect to counterfeit purchase behavior having the strong explanatory power of attitude and subjective norm on purchase intention (66.9% in Omani sample and 74.4% in Qatari sample). Several previous studies in the counterfeit domain used TRA as a theoretical base and tried to extend the theory by examining the influencing factors of customer attitude towards counterfeiting, such as moral equity and relativism (Arli et al , 2015), idealism, relativism, religiosity and consumer ethics (Jiang et al , 2018), social influencing factors (information susceptibility and normative susceptibility) and personality factors (value consciousness, perceived risk, integrity, status consumption and materialism) (Ting et al , 2016), status consumption, risk taking and brand image (Patel et al , 2022). However, to the best our knowledge, the study is very limited addressing the effect of perceived social risk and perceived performance risk on the attitude formation in the domain of non-deceptive counterfeiting, particularly using the TRA as a theoretical anchor.…”
Section: Discussionmentioning
confidence: 99%
“…A brand of a product or service always has a potential effect on buying behaviour (Seifert and Kwon, 2019;Patel et al, 2023). Managers thus need to understand internal motives leading to customers' purchase decisions (Dash et al, 2021;Jeon, 2022;Chauhan et al, 2021;Rehman and Al-Ghazali, 2022).…”
Section: Brand Imagementioning
confidence: 99%
“…Brand image is a product attribute that is linked to the brand name. The brand name depends on the product features, usage, and guidelines to (Patel et al, 2022) Brand image terdiri dari lima dimensi sebagai berikut : Brand Idenity, Brand Personality, Brand Association, Brand Atittude & Behavior, Brand Benefit & Competence (Rafirizal,2017)…”
Section: Literature Review Brand Imagementioning
confidence: 99%
“…The influence of Brand Image on Purchase intention and its impact on online purchasing decisions (Lie et al, 2022;Patel et al, 2022). The brand image helps customers understand the features and functionality and intensifies the purchase intention (Bian et al, 2011;Chand and Fei, 2021).…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
See 1 more Smart Citation